Code Mixing as Communicative Function in Sold for Silver - Raudah Arsanti (Prologue: Journal on Language and Literature, 2021)
This research studies of code mixing as communicative function in the novel Sold for Silver by Janet Lim. There are two questions proposed, they are what are the types of code mixing used and how is communicative function expressed with code mixing in the novel. The theory used in this research is sociolinguistics theory with the analysis using Wardaugh theory of code mixing; the methodology employed is qualitative research in which the researcher tried to present the issues descriptively. The researcher collected the data from the novel as the primary data of this research. The result of this research is the researcher found the type of code mixing used and it is classified into two types; intra-sententially and inter-sententially. Meanwhile, the researcher also found metalingual function, emotive function, referential function, poetic function and conative function expressed with code mixing used by the characters to show what is the meaning of the speaker in the sentence